RADIOLOGIC ASSESSMENT OF LOWER THIRD MOLAR BEFORE AND AFTER ORTHODONTIC TREATMENT - Loredana Golovcencu; Daniela Anistoroaei; Vasilica Toma; Eduard Radu Cernei; Alina Claudia Sodor Botezatu; Georgeta Zegan (Romanian Society of Oral Rehabilitation, 2019)
To assess the reliability of two predictive parameters for third lower molar prognosis for eruption or impaction and to establish relationship between them. Materials and methods. We examined the ratio between third molar available posterior space and the mesiodistal diameter of the mandibular third molar and the angulation of the long axis of the mandibular third molar with the long axis of the adjacent second molar measured on the orthopantomograms of 70 orthodontic patients before and after orthodontic treatment. The total number of molars taken into study was 130, 88 at patients who were treated without premolar extractions and 42 in patients treated by premolar extraction All the measurements were statistically analyzed for both groups and compared. Results. In the nonextraction group there was a slight increase in the posterior available space for those molars with favorable chances for eruption from the beginning, and also a positive change of angulation in the same condition. The number of molars with uncertain or low chances for eruption at the beginning of the treatment remained stable in the nonextraction group. Premolar extraction improved with 40% third lower molar angulation, increasing the chances of eruption , but has a smaller influence on the posterior available space. There is a strong inverse proportional relationship between these variables. Conclusions. The ratio between the available posterior mandibular space and the mesiodistal diameter of the lower third molar and the angle formed by the long axes of the third and second molar proved to be useful predictive measurements for mandibular third molar assessment